Carnus hemapterus (Diptera: Carnidae) - an unusual parasite on European Roller from Romania - Oboňa, Jozef; Manko, Peter; Mlynárová, Laura; Pintilioaie, Alexandru-Mihai; Topală, Laura-Elena; Hromada, Martin; Roháček, Jindřich (Annals of parasitology, 2024)
An uncommon host-parasite relationship is presented: Carnus hemapterus Nitzsch, 1818 (Diptera: Carnidae) parasiting fledgling of Coracias garrulus Linnaeus, 1758. This host association has hitherto not been recorded from the territory of Romania.
Keywords: Bird Diseases; nemoci ptáků; Animals; Romania; Rumunsko; Diptera; Host-Parasite Interactions; zvířata; interakce hostitele a parazita